Book review: The psychological complex: Psychology, politics and society in England, 1869-1939 (1985): by Nikolas Rose - van Zyl, Susan (PINS-Psychology in Society, 2025)
Psychology as social work: A response to Nikolas Rose's "The psychological complex" There may be something perverse about basing a deliberately polemical review upon a work which is neither significantly wrong nor surprisingly and originally right. Certainly Nikolas Rose's The psychological complex (1985) is neither of these controversial things.